Conductas de los agresores sexuales seriales y desconocidos: Influencias situacionales y consistencia = Behaviors of serial and unknown sex offenders: situational influences and consistency - Janosch González, Heriberto (Behavior & Law Journal, 2022)
Purpose: To study the consistency in crime scene behaviors of unknown and serial sexual offenders and the influence of situational factors. Methods: The crime scene behaviors of 18 unknown and serial sexual offenders, who committed at least 54 sexual assaults, were analyzed. They have been correlated with situational factors. The consistency of each of these behaviors was also studied. Results: Some offenders' behaviors are influenced by situational factors and, conversely, some situational factors may be influenced by such behaviors. Some behaviors that, prima facie, are not influenced by situational factors are consistent. An exception is offender sexual behaviors. Conclusion: This analysis confirms, albeit to a limited extent, expected, but never before studied, behavioral relationships in a Spanish sample of serial and unknown sex offenders.